Financial crime, corruption and tax evasion: a cross-country investigation. Issue 4 (1st October 2018) - Amara, Ines; Khlif, Hichem
Abstract : Purpose: This paper aims to examine the relationship between the financial crime and tax evasion and tests whether corruption moderates such a relationship. Design/methodology/approach: Tax evasion measure is based onSchneider et al. (2010) . Financial crime is collected from Basel anti-money laundering (AML) report. Findings: Using a sample of 120 countries, the authors find that the level of financial crime is positively associated with tax evasion. When testing for the moderating effect of corruption, they document that the positive relationship between financial crime and tax evasion is more pronounced for high corrupt environments. Originality/value: The findings have policy implications for governments aiming to combat tax evasion and financial crimes.